Prenatal Exposure to Maternal Cigarette Smoke and Offspring Risk of Excess Weight Is Independent of Both Birth Weight and Catch-Up Growth. (26th August 2012) - Gravel, Jonathan; Potter, Beth; Dubois, Lise
Abstract : Prenatal exposure to maternal cigarette smoke (PEMCS) is one of the most common insults to the developing fetus and has consistently emerged as an important risk factor for excess weight in the offspring. However, no consensus exists on the mechanism of action or duration of impact. This study seeks to further examine the role of PEMCS on overweight status of children up to age 10. Mother and child pairs (n = 1183 ) were analysed from the Québec Longitudinal Study of Child Development (QLSCD) (1998–2010). Multivariable logistic regression models were used to control for confounders and assess mediation. PEMCS was associated with overweight status at age 10 (OR: 1.70; 95% CI: 1.20–2.43) after adjustment for early life exposures and childhood behaviours. This relationship remained robust after adjustment for birth weight and catch-up growth. Other significant predictors included APGAR score, mother's immigrant and weight status, family type and child energy intake. The elevated risk of excess weight among the offspring of smoking mothers was not accounted for by other known determinants, and PEMCS appears to play a role independent of birth weight and catch-up growth. Our research suggests that young mothers may be an important audience for targeting preventive strategies.